2019
DOI: 10.1158/0008-5472.can-18-1913
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer–Instructed Stromal Fibroblasts Enhance IL23 Expression in Dendritic Cells to Support Expansion of Th17 Cells

Abstract: Persistent infection with high-risk human papillomavirus (HPV) is a prerequisite for the development of cervical cancer. HPV-transformed cells actively instruct their microenvironment, promoting chronic inflammation and cancer progression. We previously demonstrated that cervical cancer cells contribute to Th17 cell recruitment, a cell type with protumorigenic properties. In this study, we analyzed the expression of the Th17-promoting cytokine IL23 in the cervical cancer micromilieu and found CD83 þ mature den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…Unable to migrate, they produce pro-tumorigenic MMP-9 locally within the stroma [12]. Moreover, they secrete only low amounts of the Th1-polarizing cytokine IL-12 [18] potentially underlying the Th2 shift observed in cervical carcinogenesis in vivo. This indicates that deviated dendritic cells may rather contribute to tumor progression than to immune control.…”
Section: The Two Faces Of the Immune System In Cervical Cancer Develomentioning
confidence: 99%
See 2 more Smart Citations
“…Unable to migrate, they produce pro-tumorigenic MMP-9 locally within the stroma [12]. Moreover, they secrete only low amounts of the Th1-polarizing cytokine IL-12 [18] potentially underlying the Th2 shift observed in cervical carcinogenesis in vivo. This indicates that deviated dendritic cells may rather contribute to tumor progression than to immune control.…”
Section: The Two Faces Of the Immune System In Cervical Cancer Develomentioning
confidence: 99%
“…Although their exact role is still unclear, the fact that they accumulate with advanced disease stages indicates a role in cancer progression [11]. The interplay between cervical cancer-instructed fibroblasts and dendritic cells further promotes expansion of Th17 cells via the heterodimeric cytokine IL-23 [18]. Interestingly, the cytokines IL-23 and IL-12 sharing the same IL-12p40 subunit are regulated by IL-6 in an opposing manner.…”
Section: The Two Faces Of the Immune System In Cervical Cancer Develomentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that a local and/or systemic immunosuppressive microenvironment leads to the evasion of immune surveillance and promotes the development of cervical cancer 5‐15 . Some studies have indicated that an elevated level of patient‐derived immunosuppressive cells, such as T helper 17 (TH17) cells, myeloid‐derived suppressor cells (MDSCs) and regulatory T cells (Tregs), play a vital role in promoting cervical cancer progression 11‐15 . In addition, alterations in the levels or activity of CD4 + /CD8 + T cells and B cells have been suggested to be important in the immunological pathogenesis of cervical cancer 16‐18 .…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to cytotoxic T cell-mediated lysis may follow down regulation of tumour cell antigen processing or MHC expression [19]. Additionally, HPV transformed cells modulate the local immune environment to suppress effector immune responses by a wide range of mechanisms including induction from fibroblasts of immunomodulatory cytokines [20], induction of local innate M2 macrophages [21], and induction of antigen specific regulatory T cells [22]. There are thus substantial barriers to successful HPV protein targeted immunotherapy for naturally arising HPV associated malignancies in humans.…”
Section: Barriers To Effective Immunotherapymentioning
confidence: 99%